A Unique Case of Metformin-Associated Lactic Acidosis. (15th November 2018) - Gershkovich, Benjamin; McCudden, Christopher; Burns, Kevin D.
Abstract : Metformin-associated lactic acidosis [MALA] is a potentially fatal condition characterized by an elevation in serum lactate in patients with metformin exposure. An 82-year-old man with no prior renal history was brought to hospital after being found by his family in a confused state. He had a history of type 2 diabetes mellitus, and his medications included regular metformin. On arrival to our hospital he was conscious but confused and noted recent decreased oral intake. Initial investigations revealed severe acidemia (pH <6.75, undetectable bicarbonate), with elevated serum lactate, urea, creatinine, and hyperkalemia. He was treated with intravenous dextrose, crystalloids, and bicarbonate and underwent urgent hemodialysis. The patient responded well to supportive therapies and achieved full renal recovery one week after admission. He was discharged feeling well, with a new antihyperglycemic medication regimen. This case highlights the potential for life-threatening acidemia in cases of MALA. The case is further unique in that the patient was conscious and responded to questions on arrival, despite the serious metabolic disturbance, and recovered completely. From a safety standpoint, health care providers should advise and educate their patients about discontinuing metformin and other potentially harmful medications in the context of acute illness with volume contraction.